Analisis Audit Internal dalam Mendeteksi Kecurangan pada Pt. Bersama Ozora Sukses Gadai - Analisa Gulo; Ratih Anggraini Siregar (Journal of Economics and Management Scienties, 2023)
This research was conducted to find out some of the causes of fraud and also the way of auditors to minimize fraud at PT. With Ozora Pawn Success. This research uses a qualitative descriptive approach starting from observing and exploring ad flitering information thoroughly. The objects in this study are the internal auditors and several employees who work at PT. with Ozora Pawn Success. The types and sources of data used were obtained from primary data such as the results of interviews and observations, and secondary data, namely from books, the internet and existing data from previously obtained journals. Data collection techniques using documentation techniques, interviews and observations. The data analyze technique uses Nvivo qualitative data. The results of this study indicate that the cause of fraud at PT. Together with Ozora, Sukses Gadai is the weakness of the administrative system and auditor supervision and the presence of fictitious filings. The obstacle faced was the customer's weak understanding of the importance of complete filing. Which gave rise to bad credit and the auditor did not directly review the field.